Impact of Compensation, Productivity, and Service Quality on Member Satisfaction: A Quantitative Analysis: Dampak Kompensasi, Produktivitas, dan Kualitas Layanan terhadap Kepuasan Anggota: Analisis Kuantitatif - Umah, Rizdatul; Sari, Herlinda Maya Kumala (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to investigate the influence of compensation, productivity, and service quality on member satisfaction in Eccindo cooperatives. Employing a quantitative approach, purposive sampling was used to select 75 respondents from Eccindo cooperative members, and data were collected through distributed questionnaires. The data were analyzed using multiple linear regression in SPSS 20. The findings demonstrate that compensation, productivity, and service quality individually affect member satisfaction, and collectively, they have a significant impact on member satisfaction. This research underscores the importance of addressing compensation, productivity, and service quality to enhance member satisfaction in cooperatives, providing valuable insights for cooperative management and policymakers. Highlights: Compensation's Influence: Evaluate how compensation affects member satisfaction in Eccindo cooperatives. Productivity's Role: Examine the impact of productivity on member contentment within the cooperative setting. Quality of Service: Assess the significance of service quality in enhancing member satisfaction. Keywords: Compensation, Productivity, Service Quality, Member Satisfaction, Quantitative Analysis